Penerapan Teknik Penanganan yang Berbeda terhadap Kualitas Ikan Segar sebagai Bahan Baku Pembuatan Ikan Pindang - Pandit I Gde Suranaya (Jurnal Perikanan Universitas Gadjah Mada, 2017)
Histamine toxicity can be occurred after consumsing decomposing fish (pindang). The community (fishermen) perform different handling techniques on raw materials of pindang to slow down the decomposition process. This research is aimed to know the influence of various techniques of handling fish on the quality of raw materials of pindang. This research used completely randomized design with single factor. This study compared various methods of fish handling commonly used by community (fisherman in Kusamba village) to maintain the quality of raw materials of pindang, such as: kept on room temperature (technique A), add 1 kilogram crushed ice for 4 kilogram fishes (technique B), add 10% salt (technique C), and combination of technique B and C (ice and fish combination 1:8 plus 5% salt as technique D). Diversity analysis show a significant influence of different techniques of fish handling on the quality of raw material of pindang (p value <0.05). Addition of crushed ice show the best quality result among fish handling technique with histamine levels 11.30 mgN%, moisture content 74.53%, TVB 20.19 mgN%, salt 0.32%, bacteria 13 x 101 colonies / g, and negative coliform. Organoleptic assessment for B techniques also show the best result with visibility score 8.0 (bright, strong, and thin scale), eye 7.7 (convex, slightly foggy cornea, slightly faint pupil), odor 7.8 (soft odor), and texture 7.8 (elastic).